Cellular adverse actions of dibromoacetonitrile, a by-product in water bacterial control, at sublethal levels in rat thymocytes. (September 2018) - Kishida, Takumi; Akiyoshi, Kenji; Erdenedalai, Erdenebat; Enhetomuru, Anu; Imai, Shoji; Oyama, Yasuo
Abstract: The aim of this study was to investigate the effects of dibromoacetonitrile (DBAN), a by-product in water bacterial control, at sublethal concentrations on rat thymocytes, by using a cytometric technique with appropriate fluorescent dyes. By using this method, the possibility that DBAN induces cellular actions related to oxidative stress was assessed. DBAN reduced the content of cellular nonprotein thiols under Zn 2+ -free conditions. It elevated the intracellular level of Zn 2+, being independent from external Zn 2+ . DBAN increased cell vulnerability to the cytotoxic action of hydrogen peroxide. These actions of DBAN were likely related to oxidative stress. DBAN is formed by the reaction of bromides and chlorinated oxidants during water disinfection. Hydrolysis of 2, 2-dibromo-3-nitrilopropionamide, an antimicrobial used in hydraulic fracturing fluids for production of shale gas and oil, produces DBAN. Therefore, the concern regarding the levels of DBAN in industrial water systems is necessary to avoid the environmental risk to humans and wild mammals. Highlights: Adverse actions of DBAN at sublethal levels were examined in rat thymocytes. DBAN decreased cellular content of nonprotein thiols. DBAN increased intracellular Zn 2+ concentrations by intracellular Zn 2+ release. DBAN at sublethal levels increased cell vulnerability to oxidative stress. Environmental risk assessment on DBAN in industrial water may be necessary.